Concordance between child's and parents'- reported Health-related quality of life and overweight. (30th September 2020) - Esposito, F; Scrimaglia, S; Masini, S; Marini, A; Gori, D; Bragonzoni, L; Barone, G; Messina, R; Gibertoni, D; Dallolio, L
Abstract: Background: Health-related quality of life (HRQoL) of children is an important health outcome which has frequently been investigated regarding children's chronicle illnesses using parents proxy-reported HRQoL. Obesity is an increasingly frequent condition in children, for which the evidence about perceived quality of life is lacking. The aim of our study is to examine the concordance between child's and parents'- reported HRQoL according to children's weight status. Methods: A cross-sectional study was conducted in 2019 among 128 children, aged 6-10, recruited in a primary school of Imola (Italy). Children were divided in Group1 (G1: normal-underweight) and Group2 (G2: overweight-obese) using the International Obesity Task Force cut points. HRQoL was assessed using the Italian version 4.0 of Paediatric Quality of Life (PedsQL) questionnaire. We obtained self-reported children's HRQoL total score and the parents' perceived children's HRQoL total score. Each score had two subscales: one for physical health and one for emotional, social and school functioning. Results: In G1 there were 86 children and in G2 42. The correlation between the children's and parents' HRQoL scores is low in G1 (physical health: 0.24; emotional, social and school functioning: 0.15). Children in G2 and their and parents' perception of physical health are poorly correlated (r=-0.09) and those of emotional, social and school functioning are well correlated (r = 0.43).We observed that in case of discordant HRQoL results, parents usually overestimate their children's HRQoL. Conclusions: Correlation between the children's and parents' HRQoL scores is low in G1. In G2 children's and parents' perception are concordant for emotional, social and school functioning and unrelated for physical health. It would be useful to investigate whether these results depend from lack of communication between parents and children or lack of parents' awareness of health-related problems with obesity. Key messages: Parents and children have a discordant perception of physical health quality of life. Further studies should investigate the reasons why these results are discordant.